2008
DOI: 10.1017/s1368980007000286
|View full text |Cite
|
Sign up to set email alerts
|

Can working conditions explain differences in eating patterns during working hours?

Abstract: Objective: The aim of this study was to examine whether there are associations between working conditions and the use of staff canteen or packed meals among Finnish employees. Setting: Data were obtained from cross-sectional surveys on working conditions, conducted triennially (1997, 2000, 2003) since 1997. Subjects: In each survey, the subjects were 25-64-year-old employed Finnish employees: 3096 men and 3273 women. Results: Employees at large workplaces used canteens far more often than those at smaller wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 29 publications
(45 reference statements)
3
51
0
3
Order By: Relevance
“…Preparations for the system have continued as a project between the Finnish Institute for Health and Welfare (THL), Finnish Institution of Occupational Health (TTL) and the Finnish Heart Association. The project has analysed existing data on meal patterns among Finnish population groups in order to show how the current health monitoring systems could be utilized in evaluation and development of catering services (14)(15)(16)(17) . In addition, the project will search for alternative data sources, such as registers and statistics that could cost-effectively provide information on the quality of meals served outside the home.…”
Section: Monitoring the Use Of Catering Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparations for the system have continued as a project between the Finnish Institute for Health and Welfare (THL), Finnish Institution of Occupational Health (TTL) and the Finnish Heart Association. The project has analysed existing data on meal patterns among Finnish population groups in order to show how the current health monitoring systems could be utilized in evaluation and development of catering services (14)(15)(16)(17) . In addition, the project will search for alternative data sources, such as registers and statistics that could cost-effectively provide information on the quality of meals served outside the home.…”
Section: Monitoring the Use Of Catering Servicesmentioning
confidence: 99%
“…Finns with the lowest education and living somewhere outside the capital area prefer packed meals (28) . Differences in worksite canteen use defined by years of education and place of residence have not changed remarkably in Finland between 1979 and 2001 (29) .…”
Section: Workite Lunch and Eating Habits Of Adultsmentioning
confidence: 99%
“…Occupation may affect eating habits during work time, social environment and the lifestyle of colleagues. Furthermore, physical and mental work strain and degree of work control have been reported to influence eating habits (Wickrama et al, 1995;Lallukka et al, 2004;Raulio et al, 2008). Shift/night workers may in addition encounter special challenges with regard to where and what to eat.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Finnish worksite canteens are mostly used by well-educated urban people (Roos et al 2004;Raulio et al 2005;Paturi et al 2008), and that women eat packed lunches more often than men (Gronow & Jääskeläinen 2001;Raulio et al 2007;Paturi et al 2008). Employees' food choices at worksite canteens are found to be more in line with nutritional recommendations than those at other lunch places, because, for instance, fresh vegetables and fish dishes are favoured there (Lallukka et al 2001;Raulio et al 2004;Roos et al 2004).…”
Section: Introductionmentioning
confidence: 99%